2018
DOI: 10.1002/jeab.488
|View full text |Cite
|
Sign up to set email alerts
|

Baseline reinforcement rate and resurgence of destructive behavior

Abstract: Concepts from behavioral momentum theory, along with some empirical findings, suggest that the rate of baseline reinforcement may contribute to the relapse of severe destructive behavior. With seven children who engaged in destructive behavior, we tested this hypothesis in the context of functional communication training by comparing the effects of different baseline reinforcement rates on resurgence during a treatment challenge (i.e., extinction). We observed convincing resurgence of destructive behavior in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 77 publications
0
47
0
Order By: Relevance
“…Owen participated in Fisher et al (2019) before the present study. Afton was a 9-year-old girl diagnosed with attention-deficit/ hyperactivity disorder, oppositional defiant disorder, and mixed receptive-expressive language disorder.…”
Section: Subjects and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Owen participated in Fisher et al (2019) before the present study. Afton was a 9-year-old girl diagnosed with attention-deficit/ hyperactivity disorder, oppositional defiant disorder, and mixed receptive-expressive language disorder.…”
Section: Subjects and Settingmentioning
confidence: 99%
“…We programmed a VI 40-s reinforcement schedule for Owen and Afton and used a progressive-interval assessment Fisher et al, 2019) to prescribe a VI 4-s reinforcement schedule with Kendrick and a VI 8-s reinforcement schedule with Teddy. The contingencies were similar to those of the baseline in Context A, except the therapist delivered functional reinforcement for destructive behavior according to a variable-interval (VI) schedule to better control and equate reinforcement rates in the two contexts.…”
Section: Resurgence Evaluation In Contexts B and Cmentioning
confidence: 99%
“…Next, the target behavior is extinguished while an alternative behavior is reinforced. Finally, alternative reinforcement is either reduced (Craig, Browning, Nall, Marshall, & Shahan, 2017; Craig, Browning, & Shahan, 2017; Lieving & Lattal, ) or eliminated altogether (Craig, Cunningham, Sweeney, Shahan, & Nevin, ; Craig & Shahan, ; Fisher et al, ; Fisher et al (in press); Leitenberg, Rawson, & Mulick, ; Nevin et al, ). Resurgence occurs if target behavior returns in this last phase.…”
Section: Applications To Behavior‐analytic Datamentioning
confidence: 99%
“…Thus, Fisher, Greer, Fuhrman, et al showed that BMT, and quantitative models of resurgence more generally, have the ability to improve standard of care when it comes to treating problem behavior. Additional translational research by Fisher et al (), Fuhrman et al (), and Lichtblau et al (under review) supported similar predictions of BMT when treating problem behavior.…”
Section: Behavioral Momentum Theory Of Resurgencementioning
confidence: 76%
“…Given the importance of developing treatments that are durable, recent translational research on the durability of common interventions for problem behavior has generated some troubling findings. Despite their widespread use (Petscher, Rey, & Bailey, 2009;Tiger, Hanley, & Bruzek, 2008) and robust efficacy while in effect (Greer, Fisher, Saini, Owen, & Jones, 2016;Hagopian, Fisher, Sullivan, Acquisto, & LeBlanc, 1998;Kurtz, Boelter, Jarmolowicz, Chin, & Hagopian, 2011;Petscher et al, 2009;Rooker, Jessel, Kurtz, & Hagopian, 2013), differential-reinforcementbased interventions for socially reinforced problem behavior are prone to relapse when differential reinforcement is suspended (Fisher et al, 2019;Fisher, Greer, Fuhrman, Saini, & Simmons, 2018;Fuhrman, Fisher, & Greer, 2016;Harding, Wacker, Berg, Lee, & Dolezal, 2009;Lichtblau, Greer, & Fisher, under review;Mace et al, 2010;Nevin et al, 2016;Volkert, Lerman, Call, & Trosclair-Lasserre, 2009;Wacker et al, 2011). These increases in problem behavior with the suspension of differential reinforcement are examples of resurgence.…”
Section: Resurgence Following Differential Reinforcementmentioning
confidence: 99%